Service-learning in physical education teacher education: A retrospective exploratory study to examine its challenges - Salvador-Garcia, Celina; Chiva-Bartoll, Oscar; Maravé-Vivas, María; Gil-Gómez, Jesús (Teaching and teacher education, 2023)
This work is a qualitative retrospective exploratory study that aims to problematize service-learning to identify the challenges this pedagogical approach may entail in teacher education. Drawing on the narratives of 175 pre-service teachers and the data gathered by 14 teacher educators/researchers who have been applying service-learning (9 meetings - 608 min), we encountered six interconnected categories of findings (i.e., individual participants’ dispositions, complex working conditions, pedagogy, logistics, subject, other agents), within which we identified different interconnected tensions. The findings show that service-learning is complex and challenging, and we provide some suggestions to deal with the issues it entails.